Gene Loss and Error-Prone RNA Editing in the Mitochondrion of Perkinsela, an Endosymbiotic Kinetoplastid - David, Vojtěch; Flegontov, Pavel; Gerasimov, Evgeny; Tanifuji, Goro; Hashimi, Hassan; Logacheva, Maria D; Maruyama, Shinichiro; Onodera, Naoko T; Gray, Michael W; Archibald, John M; Lukeš, Julius (mBio, 2015)
UNLABELLED: Perkinsela is an enigmatic early-branching kinetoplastid protist that lives as an obligate endosymbiont inside Paramoeba (Amoebozoa). We have sequenced the highly reduced mitochondrial genome of Perkinsela, which possesses only six protein-coding genes (cox1, cox2, cox3, cob, atp6, and rps12), despite the fact that the organelle itself contains more DNA than is present in either the host or endosymbiont nuclear genomes. An in silico analysis of two Perkinsela strains showed that mitochondrial RNA editing and processing machineries typical of kinetoplastid flagellates are generally conserved, and all mitochondrial transcripts undergo U-insertion/deletion editing. Canonical kinetoplastid mitochondrial ribosomes are also present. We have developed software tools for accurate and exhaustive mapping of transcriptome sequencing (RNA-seq) reads with extensive U-insertions/deletions, which allows detailed investigation of RNA editing via deep sequencing. With these methods, we show that up to 50% of reads for a given edited region contain errors of the editing system or, less likely, correspond to alternatively edited transcripts. IMPORTANCE: Uridine insertion/deletion-type RNA editing, which occurs in the mitochondrion of kinetoplastid protists, has been well-studied in the model parasite genera Trypanosoma, Leishmania, and Crithidia. Perkinsela provides a unique opportunity to broaden our knowledge of RNA editing machinery from an evolutionary perspective, as it represents the earliest kinetoplastid branch and is an obligatory endosymbiont with extensive reductive trends. Interestingly, up to 50% of mitochondrial transcripts in Perkinsela contain errors. Our study was complemented by use of newly developed software designed for accurate mapping of extensively edited RNA-seq reads obtained by deep sequencing.
Keywords: editace RNA; Sequence Analysis, DNA; mitochondriální DNA; delece genu; Amoebozoa; DNA, Mitochondrial; Kinetoplastida; sekvenční analýza DNA; Mitochondria; RNA Editing; Gene Deletion; Computational Biology; mitochondrie; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; výpočetní biologie